The facilitators and barriers to reduce sugar sweetened beverages intake among overweight females/ Nur Islami Mohd Fahmi Teng and Ahmad Syakirin Sulong - Mohd Fahmi Teng, Nur Islami; Sulong, Ahmad Syakirin (Faculty of Health Sciences, Universiti Teknologi MARA, 2019)
Excessive energy intake and high consumption of sugar sweetened beverages (SSB) was associated with the incidence of obesity. The prevalence was higher among female as compared to male. The aim of this study was to explore the facilitators and barriers to stop consuming SSB and increase the intake of plain water. A qualitative study with semi-structured interviews were conducted twice, at baseline and after 8 weeks of intervention. The intervention regime consists of avoiding SSB intake and substitute it with plain water intake, among overweight, females, undergraduates' students. Data is also collected through self-reflected diary. The interview was audio recorded, transcribed, and analyzed using thematic content analysis approach. A total of five subjects involved in the interview. Subjects felt that desire to be healthy, other's perception and support as the facilitators for them to sustain with the intervention regimen. On the other hand, environment pressure and availability of beverages were their main barriers. Subjects also claimed they felt happy during the intervention program. In conclusion, the challenges of adherence to a healthy eating can be overcome by a strong will to be healthy. Overweight females need supports from surrounding to change their lifestyle habits.